2017
DOI: 10.18553/jmcp.2017.23.3-b.s17
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Life Expectancy for Pirfenidone in Idiopathic Pulmonary Fibrosis

Abstract: This study was funded by InterMune International AG, a wholly owned Roche subsidiary since 2014. Fisher was previously employed by InterMune UK, a wholly owned Roche subsidiary, until July 2015. He is currently employed by FIECON, which has received funding from F. Hoffmann-La Roche for consulting services. Nathan has received consulting fees from Roche-Genentech and Boehringer Ingelheim. He is also on the speakers' bureau for Roche-Genentech and Boehringer Ingelheim and has received research funding from both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 30 publications
4
74
0
2
Order By: Relevance
“…Although the novel antifibrotic agents pirfenidone and nintedanib attenuate the progressive decline in lung function characteristic of IPF [1], reduce the risk of hospitalisation or exacerbation [2,3], and reduce the risk of death [3][4][5], IPF is a very severe disease where clinical decline is common. IPF is of particular interest to the lung physiologist because its clinical expression, which ranges from exertional dyspnoea occurring early in the disease to end-stage respiratory failure, is directly related to alterations in lung physiology.…”
Section: Introductionmentioning
confidence: 99%
“…Although the novel antifibrotic agents pirfenidone and nintedanib attenuate the progressive decline in lung function characteristic of IPF [1], reduce the risk of hospitalisation or exacerbation [2,3], and reduce the risk of death [3][4][5], IPF is a very severe disease where clinical decline is common. IPF is of particular interest to the lung physiologist because its clinical expression, which ranges from exertional dyspnoea occurring early in the disease to end-stage respiratory failure, is directly related to alterations in lung physiology.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were stratified according to FVC values (FVC >90% and ⩽90%; FVC >70% and ⩽70%). As for pirfenidone, there were no statistically significant differences between these subgroups in the annual rate of decline in FVC, change from baseline in St George's Respiratory Questionnaire total score, or time to first acute exacerbation [28,30]. These results showed consistent and meaningful evidence of a similar functional decline in both categories, more preserved and less preserved lung function and, most importantly, that antifibrotic drugs are equally effective in both scenarios.…”
Section: Milestones From Clinical Trialsmentioning
confidence: 67%
“…Both for pirfenidone and nintedanib, the analyses provided further evidence to support the clinically meaningful treatment benefit and acceptable safety profile of antifibrotic treatments in patients with IPF [25,27,28].…”
Section: Milestones From Clinical Trialsmentioning
confidence: 81%
“…14 15 In addition, real-world registry data suggest improved survival in those treated with, versus without, antifibrotic treatments, regardless of baseline disease severity, 16 and pooled registry and clinical trial data suggest that pirfenidone increases life expectancy compared with best supportive care. 17 However, individuals may not tolerate adverse events (AEs) associated with pirfenidone (gastrointestinal and skin-related events) 12 14 or nintedanib (diarrhoea) 13 ; real-world data showed that AEs led to drug discontinuation in 20.9% and 26.3% of pirfenidone-treated and nintedanib-treated patients with IPF, respectively. 18 QoL is often significantly impaired in IPF, 1 9 19 and neither pirfenidone nor nintedanib has demonstrated benefits to QoL in clinical trials.…”
Section: Open Accessmentioning
confidence: 99%